The throwaway : a thriller - Moreci, Michael (Forge, 2018)
Mark Strain had it all--beautiful wife, a baby on the way, and a skyrocketing career as a D.C. lobbyist. But when Mark is violently abducted from his home by masked men, everything he knows is turned upside down. They say Mark committed treason. They say he's a traitor to the United States. They say he's a spy.